GRADIENT COMPOSITE COATINGS FOR FOR WORKING SURFACES OF PLATES OF BREAKING DEVICES - Кіндрачук, М. В.; Тісов, О. В.; Стебелецька, Н. М.; Харченко, В. В.; Костюк, Є. П. (Science-based technologies, 2014)
The paper is devoted to the theoretical and experimental investigation in order to develop a wear resistant composite coating for deposition to the working surfaces of breaking devices. The research is based on the idea of forming a positive gradien of mechanical properties of the coating. It was elaborated and tested a composite eatectic alloy based on steel 12Х18Н9Т. For better serviceability the thermalproperties of all components of the alloy were consedrered. It was also argued thet additional laser treatment of the surface contributes to better structure and tribological properties of the coating. Developed and patented a method of forming plasma coatings through their dual laser melting. It is proved that the improved properties tribotechnical twice melted coating is achieved through the formation of surface structures corresponding to the rule of a positive gradient of mechanical properties. Found that laser treatment significantly increases plasma coating adhesion strength of the material.